EARTHEN BEEHIVE DOMES OF NORTHEN SYRIA - Mecca, Saverio; Dipasquale, Letizia (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
The Vernacular Architectural Heritage is important for our own future because such architectures are characterized by a high level of technical variability and integration in geographical and cultural environments together with their traditionally ecological and effective energy performances, which is of the utmost relevance, consistent "tacit" and local knowledge. The beehive dome vernacular architectures constitute a cultural and architectural heritage, as well as a technique, shared between the Orient and the Occident. The “tholos” or “beehive” domes result from an ancient tradition of construction, which produced traditional architectures and rural and urban dwellings characterized by environmental performances in hot and dry climate regions. The Syrian architectural culture of the earthen beehive domes “qubab” is rich and varied: in Syria the houses with domes, built in adobe bricks, can be found as little groups of houses or bigger villages composed of hundreds of domes near Aleppo / Sfirs, Homs / Hama, and along the Euphrates River. There are only very few studies interested in constructions with domes in Syria, although they represent one of the most interesting particularities from the Syrian traditional architecture, and constitute an important chapter of a shared heritage in the Mediterranean area. This paper presents part of the results of the ‘Coupoles Et Habitats, Une tradition constructive entre Orient et Occident’ project, funded by EACEA of European Commission. This project, focused on a strong interdisciplinary approach, is implemented in cooperation between the Syrian authorities in charge of Culture and Heritage and a group of European specialized institutions (I, F, B, E, GR) with complementary profiles and competencies. The main objective is to document the unique historical landscape of earthen dome villages in northern Syria that has continued to express the complex relationship between the environment, people and architecture over thousands of years. A second objective is to examine the common roots between East and West demonstrated by the astonishing diffusion of corbelled architectural and building culture all over Europe and the Mediterranean.